Community relations dealing with a not in my back yard (NIMBY) context: An experimental application of situational theory of publics and social exchange theory. Issue 3 (11th July 2016) - Chung, Wonjun; Choi, Jinbong; Woo, Chang Wan; Lee, Soobum; Saindon, Christina E.
Abstract : Purpose: This paper investigates whether building a nuclear power plant in a community would inherently bring local conflict phenomena such as "not in my back yard (NIMBY)", focusing especially on the interactive effect between different types of local publics and their exposure to either a supportive or opposing message about a hypothetical local governmental plan to build a nuclear power plant on community participation intentions. Design/methodology/approach: Applying the two theoretical frameworks (situational theory of publics and social exchange theory) to NIMBY, this study used a quantitative approach by using 471 participants in a 4 (publics: active, aware, aroused or inactive) × 2 (advocacy message type: supportive or opposing message) experimental design. Findings: The results showed that regardless of message types, active publics were more likely to participate in community activities than any other public, but this group strongly opposed the harmful facility, while inactive publics continued to be inactive. However, aware and aroused publics were significantly influenced by messages. Originality/value: The rationale and findings of this research are original, as they have not been published previously, and are not being simultaneously submitted elsewhere. This research should contribute to the broad body of knowledge and practices in community-based conflict issues in terms of risk management. It is believed that the discussion and implications of the findings should raise interesting areas for further research.